Manajemen Kepala Sekolah dalam Penerimaan Peserta Didik Baru (PPDB) di SMPIT Istiqomah Global School Karawang Tahun Pelajaran 2022/2023 - Maulida Fu’adatus Sultoniya; Ajat Rukajat; Khalid Ramadhani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Acceptance of new students (PPDB) is a crucial moment for the school because it is the starting point that determines the smooth running of the school's activities. Therefore, school principals are required to implement a management function in the process of accepting new students. The formulation of the problem raised by the researcher is how the principal's management in the acceptance of new students (PPDB) at SMPIT Istiqomah Global School Karawang, what are the supporting factors and inhibiting factors in the acceptance of new students at SMPIT Istiqomah Global School Karawang, what are the results of the principal's management in the acceptance of new students at SMPIT Istiqomah Global School Karawang. This research uses a qualitative research approach and the type is descriptive research. The data sources used are primary data, namely school principals, PPDB committee, and waka curriculum, while secondary data are teachers, guardians of students, documentation, and archives. Data collection techniques in the form of observation, interviews, and documentation. The data analysis technique used by the researcher is data reduction in data presentation and drawing conclusions or evidence. To test the validity of the data, researchers used the original triangulation technique, member check, and used peer discussion. The results of this study indicate that: 1) the principal's management in accepting new students includes planning (planning what is needed, committee, time, place and implementation of PPDB). Organizing (division of tasks, online and offline PPDB and the PPDB system in the form of a selection system). Actuating (providing PPDB information through banners posted on the roadside, brochures given by students, and pamphlets through social media, during PPDB at the beginning of semester 2 (two), where PPDB is offline at the SMPIT Istiqomah Global School Karawang office and online at the link http://ppdb.igs.sch.id/. Controlling Controlling (the head oversees the PPDB process, and assessment meetings. 2) Supporting factors (facilities, clear and structured committees, and school existence) Inhibiting factors (uniforms do not match the initial size) solutions to repair without paying again 3) with good management the result is an increase in the number of new students, the implementation of PPDB goes as planned.